MENINGKATKAN MOTIVASI KERJA DENGAN IN HOUSE TRAINING DI PONDOK PESANTREN - Mastur Mastur; Miftah Ahmad (LP2M Universitas Bina Bangsa, 2024)
The Islamic boarding school was born from the big idea of ​​its founder. Making this big idea come true must be done by highly motivated human resources. Motivation as a driver for human resources to want to work by using all their abilities at work. Motivation can be created through various activities carried out by institutions, one of which is in-house training. The training carried out will increase motivation, thereby creating enthusiasm in carrying out activities so that it will have an impact on achieving the institution's targets. This research aims to determine the effect of in-house training carried out by institutions on the work motivation of training participants. The research was conducted on IHT Directors participants at the beginning of the 2023/2024 academic year, totaling 61 participants. Research using smart PLS software. The research results show that in-house training has a positive and significant effect on work motivation. These results can be seen from the t-statistic value of 8.270 which is greater than the t-table of 1.960 and the p-value of 0.000 which is smaller than 0.050. And the R-Square value is 0.315 or 31.5% of work motivation variables can be influenced by IHT, while 68.5% of work motivation variables are influenced by other variables that have not been studied